2012
DOI: 10.1002/app.38123
|View full text |Cite
|
Sign up to set email alerts
|

Structure, thermal, and mechanical properties of DDM‐hardened epoxy/benzoxazine hybrids: Effects of epoxy resin functionality and ETBN toughening

Abstract: Bifunctional, trifunctional, and tetrafunctional epoxy (EP) resins were hardened with stoichiometric amount of 4,4'-diaminodiphenyl methane in presence and absence of benzoxazine (BOX). The EP/BOX ratio of the hybrid systems was constant, viz. 50/50 wt %. For the bifunctional EP, the EP/BOX range covered the ratios 75/25 and 25/75 wt %, as well. Epoxy-terminated liquid nitrile rubber (ETBN) was incorporated in 10 wt % in the systems with trifunctional and tetrafunctional EP, and in 10, 15, and 20 wt % in the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 29 publications
4
45
0
Order By: Relevance
“…For example, blending between benzoxazine resins and epoxy resins, polyurethanes, and dianhydrides (Ref [12][13][14][15][16] was considered to be a potentially effective measure to enhance thermal or mechanical properties as well as flammability of the polymers. Furthermore, thermosetting copolymers based on benzoxazine resins and rubbers such as amine-terminated acrylonitrile-butadiene (ATBN) and epoxyterminated liquid nitrile rubber (ETBN) have been reported to provide various useful characteristics ( Ref 17,18). As an example, the combination of N-alkyl benzoxazine resin with ATBN resulted in a significant enhancement of the fracture toughness properties of the polybenzoxazine.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, blending between benzoxazine resins and epoxy resins, polyurethanes, and dianhydrides (Ref [12][13][14][15][16] was considered to be a potentially effective measure to enhance thermal or mechanical properties as well as flammability of the polymers. Furthermore, thermosetting copolymers based on benzoxazine resins and rubbers such as amine-terminated acrylonitrile-butadiene (ATBN) and epoxyterminated liquid nitrile rubber (ETBN) have been reported to provide various useful characteristics ( Ref 17,18). As an example, the combination of N-alkyl benzoxazine resin with ATBN resulted in a significant enhancement of the fracture toughness properties of the polybenzoxazine.…”
Section: Introductionmentioning
confidence: 98%
“…Although previous studies have found that the liquid rubber can improve the toughness of the polybenzoxazine ( Ref 17,18), there is very little or no information about the effect of the liquid rubber on the rheology, cure kinetics, and tribological behaviors of the polymer for self-lubricating polymer composites. Therefore, in this work, those behaviors of outstanding liquid rubber-modified polybenzoxazine composites including liquid rubber-modified polybenzoxazine filled with a fiber base, a friction modifier, and filler will be investigated in order to design tribosystems and select materials based on the wear map.…”
Section: Introductionmentioning
confidence: 99%
“…line™ FP, Binder, Tuttlingen, Germany). The long residence time at 210°C, recommended also by group of Grishchuk [14,15,18], was selected based on FT-IR analysis to achieve complete curing of both epoxy and benzoxazine resins. Transparent brownish epoxy-polybenzoxazine thin films were obtained after curing.…”
Section: Preparation Of Epoxy-polybenzoxazinementioning
confidence: 99%
“…Unfortunately, also copolymerization of benzoxazines with epoxy resins takes place at elevated temperatures [8,[10][11][12][13][14][15][16][17][18]. However, combining epoxy and benzoxazine resins seems a very perspective approach to design thermosets of enhanced properties, since also epoxy resins possess some excellent properties, such as good chemical resistance to solvents and good adhesion to many substrates [8,11,18,19]. One of promising applications may be an epoxy-benzoxazine coating for different substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The representatives of ammonia-based FRs (Grishchuk, Sorochynska et al et al 2013) are the ammonia-compounds guanidine (Jin, Xia et al et al 2014), urea, APP (Nie, Hu et al et al 2008, Wang, Liu et al et al 2009, Schartel, Weiß et al et al 2010, Liu, Zhang et al et al 2011, Lim, Mariatti et al et al 2012, Tang, Wang et al et al 2013, Qu, Wu et al et al 2014, Wang, Zhang et al et al 2014, Qin, Li et al et al 2015, Tan, Shao et al et al 2016, Matykiewicz, Przybyszewski et al et al 2017, ammonium pentaborate (Alongi andMalucelli et al 2012, Shen et al 2014) and ammonium sulfamate (Dahiya, Kandola et al et al 2013, Coquelle, Duquesne et al et al 2014, Tang, Zhang et al et al 2016. In particular, APP is the most common N-FR used as a single composition FR or as part of intumescent FRs in thermoplastics, thermosets, foams and coatings.…”
Section: Scheme 1-13 Structures Of Pdms and Possmentioning
confidence: 99%